A galacturonic acid-rich polysaccharide from Diospyros kaki peel: Isolation, characterization, rheological properties and antioxidant activities in vitro. (1st August 2023) - Cui, Yanlong; Wang, Ruiling; Cao, Siyue; Ismael, Mohamedelfatieh; Wang, Xin; Lü, Xin
Highlights: A Gal p A-rich polysaccharide (PPP-2) was obtained from persimmon peel. PPP-2 had M W of 12.28 kDa and mainly contained GalA, Ara, and Gal. The backbone of PPP-2 was composed of →4)- α -d -Gal p A-(1→ and →4)- α -d -Gal p A-6-OMe-(1→. PPP-2 was typical pseudoplastic fluid and owned weak gel behavior. PPP-2 showed good antioxidant activities in vitro . Abstract: This research elucidated the structural characteristics and antioxidant activity of a galacturonic acid-rich polysaccharide (PPP-2) isolated from Diospyros kaki peel. PPP-2 was extracted by subcritical water and subsequently purified by DEAE-Sepharose FF column. PPP-2 (12.28 kDa) mainly contained galacturonic acid, arabinose, and galactose with the molar ratios of 87.15: 5.86: 4.31. The structural characteristics of PPP-2 were revealed through FT-IR, UV, XRD, AFM, SEM, Congo red, methylation, GC/MS assay and NMR spectrum. PPP-2 owned the triple helical structure and degradation temperature of 251.09 ℃. The backbone of PPP-2 was formed by →4)-α-d -Gal p A-6-OMe-(1→ and →4)-α-d -Gal p A-(1→ with the side chains of →5)-α-l -Ara f -(1→, →3)-α-l -Ara f -(1→, →3, 6)-β-d -Gal p -(1→ and α-l -Ara f -(1→. Moreover, the inhibitory concentration (IC50 ) of PPP-2 to ABTS+, DPPH, superoxide radical and hydroxyl radical were 1.96, 0.91, 3.63, and 4.08 mg/mL, respectively. Our results suggested that PPP-2 might be a novel candidate of natural antioxidant in pharmaceuticals or functional food.